Students' Errors in Understanding Numeracy Problems:A Case Study of Kinesthetic Students - Mahardika, Candra; Anwar, Lathiful; Kusumasari, Vita (PRISMA, 2024)
Numeracy is an essential skill that needs to be developed early on. With good numeracy skills, students are expected to be able to solve problems that occur in everyday life. However, not all students are able to solve problems in the form of numeracy well, one of which is students with kinesthetic learning styles. This is because numeracy problems are presented in visual form, which is not in accordance with the kinesthetic students, who more easily process information physically or through movement. Therefore, kinesthetic students tend to make many mistakes in solving numeracy problems. Therefore, the researcher intends to analyze the errors made by kinesthetic students in solving numeracy problems in order to help teachers find solutions to these problems. This qualitative study involved private junior high school students in Malang city with kinesthetic learning styles as research subjects. Researchers used learning style test questionnaires, numeracy problem test results, and interview results to obtain data, which were then analyzed through data reduction, data presentation, and conclusion/verification. Based on the study's results, it was found that kinesthetic students made three types of errors in solving numeracy problems, namely 1) errors in understanding the problem, 2) errors in understanding the problem, and 3) errors in solving numeracy problems. These errors are caused by several things, including 1) students' lack of ability to interpret the reading, 2) students' lack of willingness to reread the problems presented, 3) the numeracy problems presented are complicated, i.e. presented with many numbers and objects, 4) students tend to rush to solve the problems so they do not do the reexamination process.